2005
DOI: 10.1111/j.1365-2141.2005.05809.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Evans syndrome

Abstract: SummaryEvans syndrome is an uncommon condition defined by the combination (either simultaneously or sequentially) of immune thrombocytopenia (ITP) and autoimmune haemolytic anaemia (AIHA) with a positive direct antiglobulin test (DAT) in the absence of known underlying aetiology. This condition generally runs a chronic course and is characterised by frequent exacerbations and remissions. First-line therapy is usually corticosteroids and/or intravenous immunoglobulin, to which most patients respond; however, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
249
2
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(260 citation statements)
references
References 70 publications
(132 reference statements)
2
249
2
7
Order By: Relevance
“…Some researchers emphasized the exclusion of an underlying disease for the definition of true ES [16], whereas others defined secondary ES based on underlying disease; we agree with the latter definition. ES is more than a coincidental combination of immune cytopenias; rather, it is a chronic state of profound dysregulation of the immune system [17].…”
Section: Sarper Et Al Autoimmune Hemolytic Anemia In Children and Adsupporting
confidence: 68%
See 3 more Smart Citations
“…Some researchers emphasized the exclusion of an underlying disease for the definition of true ES [16], whereas others defined secondary ES based on underlying disease; we agree with the latter definition. ES is more than a coincidental combination of immune cytopenias; rather, it is a chronic state of profound dysregulation of the immune system [17].…”
Section: Sarper Et Al Autoimmune Hemolytic Anemia In Children and Adsupporting
confidence: 68%
“…Prior to his diagnosis of AIHA, despite thrombocytopenia he did not have any bleeding and perianal infections rarely had a negative affect on his quality of life. In contrast to our observation, some researchers reported that the role of splenectomy has never been established in ES and remissions last only 1-2 months without support [16,[18][19][20]. In a survey of ES mainly from the US and Canada 15 patients underwent splenectomy at a median age of 10 years (range: 1.2-26.5 years).…”
Section: Sarper Et Al Autoimmune Hemolytic Anemia In Children and Adcontrasting
confidence: 43%
See 2 more Smart Citations
“…Steroids and IVIg are the usual first-line therapy of the ITP; anti-D is contraindicated. Rituximab, cyclosporine, mycophenolate mofetil, splenectomy (not recommended in children) and combination chemotherapy have been used in second-line treatment [14].…”
Section: Introductionmentioning
confidence: 99%